The Practices of Teachers in the Development of Post-Secondary Skills in Students with Learning Disabilities - Taylor, Sara (Journal of the American Academy of Special Education Professionals, 2021)
After high school, the outcomes for youth with disabilities fail to keep up with their typically developing peers. Participation in post-secondary education, hourly earnings, and engagement in either education or employment up to six years after high school are all lower than the general population (Cameto et al., 2011). A researcher-developed online survey investigated the current strategies used with students with Specific Learning Disabilities (SLD). The questions focused on the development of skills necessary to meet post-secondary education, employment, and independent living goals. A directed content analysis did not reveal evidence that teachers are using the evidence-based practices described by the National Technical Assistance Center on Transition. The paper includes the practices of respondents. This research shows that there is a significant difference in the practices of teachers when it comes to students with SLD. These differences may contribute to decreased post-secondary engagement. There is also a lack of research and evidence-based practices for this population leading teachers to pull from unreliable sources or ignore the need for transition skills.